2017
DOI: 10.3389/fmolb.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

Theory Meets Experiment: Metal Ion Effects in HCV Genomic RNA Kissing Complex Formation

Abstract: The long-range base pairing between the 5BSL3. 2 and 3′X domains in hepatitis C virus (HCV) genomic RNA is essential for viral replication. Experimental evidence points to the critical role of metal ions, especially Mg2+ ions, in the formation of the 5BSL3.2:3′X kissing complex. Furthermore, NMR studies suggested an important ion-dependent conformational switch in the kissing process. However, for a long time, mechanistic understanding of the ion effects for the process has been unclear. Recently, computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Antibacterial activity is usually attributed to electrostatic interactions between cations and the negatively charged membrane surface of bacteria and/or to other interactions between the cations and the bacteria's RNA/DNA proteins [11][12][13][14][15][16][17][18][19]. As a result, antibacterial coatings usually contain positively charged materials in the form of either small molecules (mostly metal ions such as copper [11][12][13]17,[19][20][21][22], silver [17,18,21], zinc [21,23,24], cobalt [25], nickel [26] or polyoxometalates [27,28]), nanoparticles (such as silver-based nanoparticles [15,[29][30][31], rubidium-silver-titanium oxide nanocomposites [32], phenol-based nanoparticles [33] or silica-based nanoparticles [31,[34][35][36][37]) or polymeric (such as chitosan/chitin [38,39], modified poly(ethylene imine) [40][41][42][43], quaternary ammonium containing polymers…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity is usually attributed to electrostatic interactions between cations and the negatively charged membrane surface of bacteria and/or to other interactions between the cations and the bacteria's RNA/DNA proteins [11][12][13][14][15][16][17][18][19]. As a result, antibacterial coatings usually contain positively charged materials in the form of either small molecules (mostly metal ions such as copper [11][12][13]17,[19][20][21][22], silver [17,18,21], zinc [21,23,24], cobalt [25], nickel [26] or polyoxometalates [27,28]), nanoparticles (such as silver-based nanoparticles [15,[29][30][31], rubidium-silver-titanium oxide nanocomposites [32], phenol-based nanoparticles [33] or silica-based nanoparticles [31,[34][35][36][37]) or polymeric (such as chitosan/chitin [38,39], modified poly(ethylene imine) [40][41][42][43], quaternary ammonium containing polymers…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study on the effects of Mg 2þ in RNA folding showed that the high concentration of Mg 2þ in liver may play a critical role in promoting the formation of an RNA kissing complex, a structure essential for efficient hepatitis C viral replication. This result suggests that Mg 2þ -dependent structural equilibrium may be an adaptive property of the hepatitis C genomic RNA (97)(98)(99). Furthermore, the results from the current study, including the analytical formulas for the dehydration free energy, may serve as a useful starting point for a systematic development of the dehydration free energy as a function of the structure environment of the binding site.…”
Section: Discussionmentioning
confidence: 68%
“…When such ions switch positions with the original cell ones, they cause denaturation and/or other structural damage. Moreover, when a metal ion is placed between two particles with hydrogen bonds, a replacement of the hydrogen occurs and then the pH of the surroundings increases [9,18,19]. While these are the major explanations for copper and silver antiviral and antibacterial properties, some other explanations were suggested in the literature, for both these ions and others [9,16,20,21].…”
Section: Introductionmentioning
confidence: 99%